A comparative study of the distribution of C₃ and C₄ species of Cyperaceae in South Africa in relation to climate - Chuba, David (Department of Biological Sciences, 2017)
In this study the contribution of the climatic factors such as temperature, altitude, and mean annual precipitation as well as phylogeny to the determination of the distribution of C₃ and C₄ genera of Cyperaceae in South Africa has been investigated. Multiple regression analysis was used to determine the climatic factor that best predicted percent C₄ distribution. To see if the C₄ syndrome was inﬂuenced by taxonomy, the percentages of C₄ species was determined for each of the subtribes and genera. The results show that the relationship between the climatic factors and percentage of C₄ Cyperaceae species is similar to what has been found for the grasses (Vogel et al., 1978). However C₃ species of Cyperaceae seem to be abundant in most parts of South Africa. Only minimum growing season temperature showed significant correlation (P = 0.000391) with percentage C₄. The presence of the C₄ syndrome is shown to have some consistency within subfamilies, tribes and genera.